The IASLC Lung Cancer Staging Project: Proposals for Revision of the TNM Stage Groupings in the Forthcoming (Eighth) Edition of the TNM Classification for Lung Cancer. Issue 1 (January 2016) - Goldstraw, Peter; Chansky, Kari; Crowley, John; Rami‐Porta, Ramon; Asamura, Hisao; Eberhardt, Wilfried E.E.; Nicholson, Andrew G.; Groome, Patti; Mitchell, Alan; Bolejack, Vanessa; Goldstraw, Peter; Rami‐Porta, Ramón; et al.
Abstract : ABSTRACT : The IASLC Staging and Prognostic Factors Committee has collected a new database of 94, 708 cases donated from 35 sources in 16 countries around the globe. This has now been analysed by our statistical partners at Cancer Research And Biostatistics and, in close collaboration with the members of the committee proposals have been developed for the T, N, and M categories of the 8th edition of the TNM Classification for lung cancer due to be published late 2016. In this publication we describe the methods used to evaluate the resultant Stage groupings and the proposals put forward for the 8th edition.